2017
DOI: 10.1155/2017/1403054
|View full text |Cite
|
Sign up to set email alerts
|

The Immunoexpression of Glucocorticoid Receptors in Breast Carcinomas, Lactational Change, and Normal Breast Epithelium and Its Possible Role in Mammary Carcinogenesis

Abstract: The role of estrogen and progesterone receptors in breast cancer biology is well established. In contrast, other steroid hormones are less well studied. Glucocorticoids (GCs) are known to play a role in mammary development and differentiation; thus, it is of interest to attempt to delineate their immunoexpression across a spectrum of mammary epithelia. Aim. To delineate the distribution pattern of glucocorticoid receptors (GRs) in malignant versus nonmalignant epithelium with particular emphasis on lactational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…However, breast cancer was one of the types of cancer not showing any difference between HSD11B1/2 expression between cancer and matched normal epithelial tissues, which suggest a paracrine, possibly by adjacent adipose tissue, instead of an autocrine effect by cortisol ( 54 ). In the same order of ideas, immunohistochemistry of 11β-HSD1 showed a presence of the enzyme in 64% of breast tumors and 97% of matched adjacent tissue ( 56 ) and GR protein amount was higher in breast tumor than in normal epithelial tissue ( 57 ). Increases in GC, particularly cortisol, can induce aromatase expression via the GRE on exon I.4 ( 26 ).…”
Section: Discussionmentioning
confidence: 74%
“…However, breast cancer was one of the types of cancer not showing any difference between HSD11B1/2 expression between cancer and matched normal epithelial tissues, which suggest a paracrine, possibly by adjacent adipose tissue, instead of an autocrine effect by cortisol ( 54 ). In the same order of ideas, immunohistochemistry of 11β-HSD1 showed a presence of the enzyme in 64% of breast tumors and 97% of matched adjacent tissue ( 56 ) and GR protein amount was higher in breast tumor than in normal epithelial tissue ( 57 ). Increases in GC, particularly cortisol, can induce aromatase expression via the GRE on exon I.4 ( 26 ).…”
Section: Discussionmentioning
confidence: 74%
“…Studies have acknowledged that full-term pregnancy decreases the risk of breast cancer [1,[11][12][13]. Due to the presence of significantly high hPL levels towards the end of gestation [2,4,6], studies have suggested that hPL contributed to this protective effect [1,14].…”
Section: Discussionmentioning
confidence: 99%
“…A variety of cancer cells such as liver, breast and ovarian cancer cells express receptors for glucocorticoids from the HPA axis and catecholamines from the SNS (55)(56)(57). The overexpression of glucocorticoid receptors has been identified as a potent survival pathway in breast cancer cells, and a study revealed that glucocorticoid receptor-mediated cancer cell survival signaling was activated by the administration of synthetic glucocorticoids as a premedication in chemotherapy treatment, which could potentially attenuate the effectiveness of chemotherapy (58). EPI and NE act as the physiological agonists for β-adrenergic receptors, with EPI preferentially binding to β 2 -adrenergic receptors and NE binding with higher affinity to β 1 -adrenergic receptors (59).…”
Section: Discussionmentioning
confidence: 99%